THE INTEGRATION OF MORAL VALUES IN ISLAMIC EDUCATION AS THE FOUNDATION FOR SUSTAINABLE COMMUNITY DEVELOPMENT - Rianto, Muhammad Ikbal; Cahnia, Dian; Baiti, Nur; Satra, Alihan (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This article analyzes the role of noble character as a foundational pillar in sustainable community development using a literature review approach. Values such as honesty, responsibility, empathy, and tolerance are identified as essential in shaping a just, harmonious, and resilient society. The study compiles recent literature from scientific journals, books, and articles to evaluate the contribution of moral values to social, economic, and environmental dimensions of development. Findings reveal that Islamic education plays a strategic role in internalizing moral values from an early age through synergy between schools, families, and communities. However, the study is limited by the lack of direct empirical data, suggesting the need for future research to explore the practical implementation of moral values across different sectors. The article emphasizes that sustainable development must be rooted in a value-based framework, not solely focused on economic growth. Artikel ini menganalisis peran akhlak mulia sebagai fondasi utama dalam pengembangan masyarakat berkelanjutan dengan pendekatan studi pustaka. Nilai-nilai seperti kejujuran, tanggung jawab, empati, dan toleransi dipandang sebagai elemen esensial dalam membentuk masyarakat yang adil, harmonis, dan berdaya saing. Studi ini menghimpun literatur dari jurnal ilmiah, buku, dan artikel terkini untuk mengevaluasi kontribusi akhlak terhadap dimensi sosial, ekonomi, dan lingkungan dalam pembangunan. Hasil penelitian menunjukkan bahwa pendidikan Islam memiliki peran strategis dalam menginternalisasi nilai-nilai moral sejak dini melalui sinergi antara sekolah, keluarga, dan masyarakat. Namun, keterbatasan kajian ini terletak pada belum tersedianya data empiris secara langsung, sehingga penelitian lanjutan disarankan untuk mengeksplorasi penerapan nilai-nilai akhlak secara praktis di berbagai sektor kehidupan. Artikel ini menegaskan bahwa pembangunan yang berkelanjutan harus berakar pada sistem nilai, bukan hanya berorientasi pada pertumbuhan ekonomi.